Persistent and Chronic Postoperative Opioid Use in a Cohort of Patients with Oral Tongue Squamous Cell Carcinoma. Issue 5 (14th October 2019) - Cata, Juan P; Patino, Miguel; Gorur, Aysegul; Du, Kim N; Uhelski, Megan L; Myers, Jeffrey; Lai, Stephen; Rubin, M Laura; Dougherty, Patrick M; Owusu-Agyemang, Pascal
Abstract: Background: Recently, the concept of persistent postsurgical opioid use has been described for patients undergoing cancer surgery. Our hypothesis was based on the premise that patients with oral tongue cancer require high dosages of opioids before, during, and after surgery, and thus a large percentage of patients might develop persistent postsurgical opioid use. Methods: After institutional review board approval, we conducted a retrospective study that included a cohort of patients with oral tongue cancers who underwent curative-intent surgery in our institution. Multivariable logistic regression models were fit to study the association of the characteristics of several patients with persistent (six months after surgery) and chronic (12 months after surgery) postoperative opioid use. Results: A total of 362 patients with oral tongue malignancies were included in the study. The rate of persistent use of opioids after surgery was 31%. Multivariate analysis showed that patients taking opioids before surgery and those receiving adjuvant therapy were 2.9 and 1.78 times more likely to use opioids six months after surgery. Fifteen percent of the patients were taking opioids 12 months after surgery. After adjusting for clinically relevant covariates, patients complaining of moderate tongue pain before surgery and those taking opioids preoperatively had at least three times higher risk of still using these analgesics one year after surgery. Conclusions: Patients with oral tongue cancers have a high risk of developing persistent and chronic postsurgical opioid use.